Cytotoxic effect of Efavirenz in BxPC-3 pancreatic cancer cells is based on oxidative stress and is synergistic with ionizing radiation - Hecht, Markus (Oncol Lett, 2018)
The non-nucleoside reverse transcriptase inhibitor (NNRTI) Efavirenz is frequently used in human immunodeficiency virus treatment, but also efficient against cancer in mouse models. Its radiosensitizing effect makes it a promising drug for combination with radiotherapy. The efficacy of Efavirenz combined with irradiation was assessed with immunostaining of DNA-damage markers and colony formation assays in BxPC-3 pancreatic cancer cells. Gene expression and protein phosphorylation of the Efavirenz-sensitive BxPC-3 cells was compared to the resistant primary fibroblasts SBL-5. Oxidative stress, mitochondrial damage and cell death were studied with live-cell microscopy and flow cytometry. Combined Efavirenz and radiation significantly increased the number of γH2AX and phospho-ataxia telangiectasia mutated foci. Efavirenz and ionizing radiation had a synergistic effect using the clonogenic survival assay. Efavirenz selectively induced cell death in the BxPC-3 cells. The differing gene expression of cell cycle and apoptotic regulator genes in both cell cultures after Efavirenz treatment match with this selective effect against cancer cells. In the phosphoprotein array, an early phosphorylation of extracellular signal-related kinase 1/2 and p38 mitogen-activated protein kinase was notably detected in the cancer cells. The phosphorylation of AKT decreased in the cancer cells whereas it increased in the fibroblasts. Oxidative stress and mitochondrial membrane depolarization appeared in the cancer cells immediately after Efavirenz treatment, but not in the fibroblasts. Efavirenz has an anti-cancer effect against pancreatic cancer mainly by the induction of oxidative stress. The antitumor potential of Efavirenz and radiotherapy are additive.